Functional Analysis and Treatment of Pica on a Preschool Playground - Ledford, Jennifer R. (Behav Anal Pract, 2018)
Appropriate use of function-based assessments and interventions is crucial for improving educational outcomes and ensuring the well-being of children who engage in dangerous problem behaviors such as pica. A function-based assessment was conducted for a child engaging in pica in an inclusive childcare setting. Results suggest pica was maintained by access to adult attention. Function-based interventions were developed, assessed, and shared with the child’s teaching team. Follow-up data suggest that his teachers continued to use the intervention and that levels of pica remained low.